Effects of nanoparticle additives to diesel on the combustion performance and emissions of a flame tube boiler. (15th October 2016) - Sungur, Bilal; Topaloglu, Bahattin; Ozcan, Hakan
Abstract: This paper presents an experimental study about the effects of nanoparticles added to diesel fuels on the combustion performance and emissions of a flame tube boiler. Nanodiesel fuels were prepared by adding aluminum oxide (Al2 O3 ) and titanium oxide (TiO2 ) nanoparticles. The performance and emissions measurements were realized in a residential, water-cooled, reversal flame tube boiler. The temperature distributions in the combustion chamber, combustion performance and exhaust gas emissions of nanodiesel with 100, 200 and 300 ppm nanoparticles were studied and these were compared with the neat diesel fuel. The results showed that addition of nanoparticles decreased the size of the peak temperature zones and increased the thermal efficiency slightly from about 90.4% to 90.9% with addition of nanoparticles up to 300 ppm. CO emissions decreased up to 200 ppm from 275 to 75 ppm by using 300 ppm Al2 O3 nanoparticles, and decreased up to 50 ppm from 275 to 225 ppm by using 300 ppm TiO2 nanoparticles. It was observed that nanodiesels did not affect the NOx emissions significantly, which were about 47–51 ppm. The results of Al2 O3 and TiO2 nanoadditives showed similar trends, but Al2 O3 nanodiesel has a bit better performance and emission characteristics compared to TiO2 nanodiesel. Highlights: The addition of nanoparticles decreased the size of the peak temperature zones. Using 300 ppm nanoparticles increased efficiency from about 90.4% to 90.9%. CO emissions decreased 200 ppm from 275 to 75 ppm by using 300 ppm Al2 O3 . NOx emissions did not change significantly, remained by about 47–51 ppm. Al2 O3 nanodiesel showed slightly better performance compared to TiO2 nanodiesel.